1966
DOI: 10.1139/v66-359
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Alkoxy Radicals: I. Hydrogen Atom Abstraction From Substituted Toluenes

Abstract: The relative rates of hydrogen atom abstractio~l from ten substituted toluenes by t-butoxy radicals in carbon tetrachloride a t 40 OC have been measured and the data fitted to the Hammett equation. A much better correlation is obtained with the a+ constants than with the u constants of the substituents. In this respect, therefore, the reaction is similar to the majority of hydrogen atom abstraction reactions by radicals of moderate and high electron affinity. That is, the polar properties of the substituents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This suggestion is consistent with work that has shown that substituent effects can be adequately correlated with + constants. 16 The fact that steric effects dominate over electronic effects in our system can be explained by a closer examination of our substrates. The compounds studied here have a bulky group that can hinder the approach of the abstracting radical, thus raising the energy of the transition state sufficiently to compensate for any electronic stabilization of the transition state by the electrondonating groups.…”
Section: Figurementioning
confidence: 91%
See 1 more Smart Citation
“…This suggestion is consistent with work that has shown that substituent effects can be adequately correlated with + constants. 16 The fact that steric effects dominate over electronic effects in our system can be explained by a closer examination of our substrates. The compounds studied here have a bulky group that can hinder the approach of the abstracting radical, thus raising the energy of the transition state sufficiently to compensate for any electronic stabilization of the transition state by the electrondonating groups.…”
Section: Figurementioning
confidence: 91%
“…The notion of a polar transition state (polar effect) has been used to explain the reactivity of substituted toluenes toward tert-butoxyl radical. 15,16 These data suggest that the transition state for hydrogen atom abstraction by the tert-butoxyl radical from substituted toluenes involves some polar character (i.e., a zwitterionic state). This suggestion is consistent with work that has shown that substituent effects can be adequately correlated with + constants.…”
Section: Figurementioning
confidence: 95%
“…31 In our opinion, the use of s + -constants is really more effective as far as the properties of radical cations are concerned but this is not that obvious for neutral radicals. Nevertheless, radical bromination of substituted toluenes with bromine, 24 N-bromosuccinimide 24 and bromotrichloromethane 32 as well as the quantitative interpretation of abstraction of a hydrogen atom by alkoxy radicals, 11,12,33 chlorine atoms, 34 and peroxy radicals 34 have become classical examples of successful use of the s + constants in free-radical chemistry. Experimental results obtained by one of the authors of this review have confirmed the exceptionally high efficiency of the s + constants in correlations with single-electron reduction potentials of various aromatic molecules and radicals.…”
Section: Correlation Analysis For Reactions Involving Free Radicalsmentioning
confidence: 99%
“…The new topological approach developed on the basis of the above models, which allows the substituent effect to be expressed in terms of discrete atomic contributions, was first reported in our publication and called r 72 -analysis. 220 Since both the steric and inductive constants were expressed in Eqns (11) and (12) as functions of 1/r 72 , the two-parameter Taft equation…”
Section: Combinational Approach R 72 -Analysis Ionisation Energies Of...mentioning
confidence: 99%
“…A recent report by Kennedy and Ingold (1) states that a Hammett po relationship affords a better correlation with ot constants than with o constants for hydrogen abstraction by tertbutoxy radicals from substituted toluenes. This result differs from earlier observations (2,3).…”
mentioning
confidence: 99%